Cost Benefit Evaluation Training for Developing Sandfish (Holoturia scraba) Cultivation Business in the Salterai Group, Tual City - Picaulima, Simon M.; Letsoin, Petrus P.; Tomatala, Pitjon (Agrikan Jurnal Agribisnis Perikanan, 2025)
The sandfish (Holoturia scrabra) cultivation business was established by the Salterai group in 2018. The business has experienced a significant increase in fixed and working capital. The fixed capital includes investment costs, while the working capital issued to obtain production factors includes fixed and variable costs. However, until now, the Salterai group has not been able to conduct an evaluation or cost-benefit analysis due to limited knowledge and understanding of the cost-benefit. The purpose of the training is to provide knowledge and understanding to the Salterai group in evaluating the cost-benefit of the sandfish cultivation business. The stages and methods used in the survey with interview, observation, and documentation methods, the training implementation with lecture, discussion, and direct practice methods, then the evaluation with quantitative descriptive methods. Community service activities went well according to the stages. The results obtained at the survey stage were the identification of investment costs and operational costs of the sandfish, H. scabra cultivation business, at the implementation stage it showed that the training was running well and smoothly so that it produced optimal social and economic benefit information, and the evaluation stage showed an increase in knowledge and understanding in evaluating the cost benefits of the sandfish H. scabra cultivation business.